The value of endobronchial ultrasound-guided transbronchial needle aspiration for the diagnosis of pulmonary sarcoidosis real life-settings - Cosgun, Ibrahim Guven; Balci, Aydin; Cilekar, Sule (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Endobronchial ultrasonography-assisted transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive technique that is used in the diagnosis of mediastinal and hilar lymphadenopathy. The aim of this study was to investigate the diagnostic value of EBUS-TBNA in the diagnosis of sarcoidosis.Methods: The study included 42 patients who underwent EBUS-TBNA because of suspected sarcoidosis (Grade I and II) on pulmonary radiography and thorax tomography. A total of 104 lymph node stations were sampled from 42 patients.Results: A diagnosis of sarcoidosis was made histologically in 38 of the 42 patients from whom lymph node sampling was performed with EBUS-TBNA.Conclusion: EBUS-TBNA was seen to be an extremely successful method in the diagnosis of Grade I and Grade II sarcoidosis. Therefore, EBUS-TBNA should be considered first in the histopathological diagnosis of Grade I and Grade II sarcoidosis.